Antibacterial effect of mouthwashes against Streptococcus mutans, Staphylococcus aureus and Enterococcus faecalis - Vanessa de Sousa; Orlando Aguirre Guedes; Lucas Rodrigues de Araújo Estrela; Luis Evaristo Ricci Volpato; Alexandre Meireles Borba; Cyntia Rodrigues de Araújo Estrela (Revista Sul-Brasileira de Odontologia, 2021)
Mouthwashes are one of the resources for controlling oral microbiota. They can reduce microorganisms, because they have antibacterial action and can access microorganisms even in areas of greater difficulty in the oral cavity. Objective: Antibacterial effect of some mouthwashes commonly used–0.12% chlorhexidine gluconate, 0.07% cetylpyridinium chloride, a solution based on essential oils (Listerine Zero), a solution of 1.33 mg benzethonium chloride / 25 mg hydrochloride lidocaine, a solution-based essential oils (Malvatricin) and 0.12% chlorhexidine + cetylpyridinium (Noplax)–was evaluated by means of agar diffusion and direct exposure tests. Material and methods: Strains of Streptococcus mutans (ATCC 27853), Staphylococcus aureus (ATCC 6538) and Enterococcus faecalis (ATCC 29212) were used in this study. For the agar diffusion test, Petri dishes with brain heart infusion agar (BHIA) were inoculated with the microbial suspensions. Sterile paper disks were immersed in the experimental for 1 min and then placed on the surface of BHIA. After incubation at 37ºC for 48 h, the diameters of the microbial inhibition halos were measured. For direct exposure test, no. 50 sterile absorbent paper points were immersed in the bacterial suspension for 5 min and then placed in Petri dishes and covered with 10 Ml of one of the tested solutions. At intervals of 1, 5, 10 and 30 min, absorbent paper points were removed from contact with substances and immersed in 7 mL of Letheen Broth and incubated at 37ºC for 48 h. Microbial growth was assessed by the turbidity of the culture medium. Results: The agar diffusion test showed inhibition halos greater than 10 mm for all substances against bacteria. In the direct exposure test, 0.12% chlorhexidine gluconate, 0.07% cetylpyridinium chloride, and 0.12% chlorhexidine associated with cetylpyridinium showed antibacterial effect on all the tested microorganisms after 10 min. Conclusion: The tested solutions showed antimicrobial effect on the biological indicators. The solutions of 0.12% chlorhexidine gluconate, 0.07% cetylpyridinium chloride and 0.12% chlorhexidine associated with cetylpyridinium showed antimicrobial effect on all biological indicators after 10 min.